Morphological influences on the photocatalytic activity of a CsTaWO6 model system - Weller, Tobias; Justus Liebig University Giessen (My University, 2017)
In the present work, the influence of different morphologies on the photocatalytic activity of a semiconducting transition metal oxide was investigated. The quaternary photocatalyst caesium tantalum tungstate (CsTaWO6) was therefore used as a model system. This compound exhibits a number of advantages compared to other photocatalysts such as titanium dioxide (TiO2) due to its crystallization in just one cubic crystal structure and its beneficial band positions for the test reaction of photocatalytic hydrogen generation. CsTaWO6 was nanostructured via hydrothermal and sol-gel processes to investigate the influence of surface area, crystallinity and pore sizes on the photocatalytic activity. It was possible to synthesize single crystal CsTaWO6 nanoparticles with different crystallite sizes and mesoporous materials with a number of pore sizes, pore ordering and resulting surface areas. When looking at the photocatalytic hydrogen evolution of all the investigated samples, it could be shown that an increase in surface area does not correlate with an increase in activity. In fact, the optimum crystallite size was found to be the most important aspect in nanostructured photocatalyst, whereas for CsTaWO6 this optimum lies at 12 to 13 nm. Furthermore, it could be shown that larger pores lead to an enhanced hydrogen production in mesoporous photocatalysts. In general, a decrease of the synthesis temperature resulted in an increase in the defect concentration (estimated from strain parameters) and therefore a lower activity. The optimum morphology for the CsTaWO6 system was found to be a mesoporous material with large pores (up to 40 nm), thin pore walls and an optimum crystallite size of approximately 12 nm.

In der vorliegenden Arbeit wurde der Einfluss unterschiedlicher Morphologie auf die photokatalytische Aktivität eines halbleitenden Übergangsmetalloxids untersucht. Dazu wurde der quaternäre Photokatalysator Cäsiumtantalwolframat (CsTaWO6) als Modellsystem verwendet. Diese Verbindung besitzt gegenüber anderen Photokatalysatoren wie Titandioxid (TiO2) den Vorteil, dass es nur in einer einzigen, kubischen Kristallstruktur kristallisiert und zudem über Bandpositionen verfügt, die für die Testreaktion der photokatalytischen Wasserstoffproduktion optimal liegen. CsTaWO6 wurde über Hydrothermal- und Sol-Gel-Synthesen nanostrukturiert, um den Einfluss von Oberfläche sowie Kristallit- und Porengröße auf die photokatalytische Aktivität zu überprüfen. Dabei konnten einkristalline CsTaWO6-Nanopartikel in unterschiedlichen Kristallitgrößen hergestellt werden, sowie mesoporöse Materialien mit einer Reihe von Porengrößen, Porenordnung und daraus resultierenden Oberflächen. Bei Betrachtung der photokatalytischen Wasserstoffentwicklung aller präparierten Proben konnte gezeigt werden, dass eine Oberflächenvergrößerung nicht mit einer Vergrößerung der Aktivität korreliert. Vielmehr kann die optimale Kristallitgröße als wichtigster Aspekt in nanostrukturierten Photokatalysatoren angesehen werden, wobei dieser Wert im Falle des CsTaWO6 bei 12 bis 13 nm liegt. Zudem konnte herausgefunden werden, dass große Poren in mesoporösen Photokatalysatoren zu einer verbesserten Wasserstoff¬entwicklung beitragen. Die Abhängigkeit der Synthesetemperatur auf die Aktivität wurde auf die steigende Defektkonzentration mit sinkender Temperatur zurückgeführt, wobei mit dieser auch die photokatalytische Wasserstoffproduktion abnahm. Als optimale Morphologie konnte für CsTaWO6 ein mesoporöses Material mit großen Poren (bis 40 nm), dünnen Porenwänden und Kristallitgrößen um das für CsTaWO6 gefundene Optimum von 12 nm bestimmt werden.
Über den Einfluss unterschiedlicher Morphologie auf die photokatalytische Aktivität einen CsTaWO6 Modellsystems
Keywords: Photokatalyse; Nanostrukturierung; Defekt-Pyrochlor-Struktur; CsTaWO6; Nanopartikel; Mesoporen; photocatalysis; nanostructuring; defect pyrochlore structure; CsTaWO6; nanoparticles; mesoporosity; ddc:540